THE COGNITIVE BENEFITS OF BILINGUALISM - Isanova Zebuniso Shavkatovna (International Journal of Literature and Language Studies, 2026)
Bilingualism has become increasingly common in today’s interconnected world. The ability to use two languages proficiently offers numerous advantages beyond communication. This article examines the cognitive benefits of bilingualism, focusing on its impact on executive functions, memory, attention, problem-solving abilities, and cognitive flexibility. Research findings indicate that bilingual individuals often demonstrate enhanced mental abilities compared to monolinguals. The study highlights the significance of bilingualism in education and cognitive development and emphasizes its role in promoting lifelong brain health.